Correction: Otic, C.J.C.; Yonemura, S. Effect of Different Surface Microstructures in the Thermally Induced Self-Propulsion Phenomenon. Micromachines 2022, 13, 871 - Clint John Cortes Otic; Shigeru Yonemura (Micromachines, 2022)
The authors wish to make the following corrections to the published paper [...]